1989
DOI: 10.1038/sc.1989.73
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the electroejaculation procedure on sperm motility

Abstract: Electroejaculation is becoming more available for obtaining semen from spinal cord injured men wishing to father children. This study was undertaken to determine what effect the electroejaculation procedure itself had on sperm motility. Factors which were found to impact on sperm motility were osmolarity, electric current and aqueous jelly lubricant used for bladder catheterisation. pH did not affect sperm motility.Key words: Infertility; Electroejaculation; Sperm motility.There has been renewed enthusiasm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…This could be the result of a deleterious eect of the electric current. Indeed, Linsenmeyer et al 14 showed that the current had a negative eect upon the motility of spermatozoa. In vitro, after a 2 min application of a 100 mA current, the spermatozoa exposed to the current are less motile than those that are not exposed.…”
Section: Discussionmentioning
confidence: 99%
“…This could be the result of a deleterious eect of the electric current. Indeed, Linsenmeyer et al 14 showed that the current had a negative eect upon the motility of spermatozoa. In vitro, after a 2 min application of a 100 mA current, the spermatozoa exposed to the current are less motile than those that are not exposed.…”
Section: Discussionmentioning
confidence: 99%
“…33 Further studies to elucidate the cause The signi®cant dierence between the better semen parameters of the antegrade rather than retrograde ejaculate, might be explained by the fact that the former semen is not contaminated with urine and is`fresher'. 35 There was no signi®cant improvement concerning sperm quality parameters after repeated stimulations.…”
Section: Discussionmentioning
confidence: 99%
“…The catheter is inserted using normal saline as a lubricant to avoid possible problems associated with the use of lubricant gels. 24,27 Prior to the introduction of this technique a bu er solution (HEPES/HTF Bu er, North Shore ART, Sydney) was instilled into the emptied bladder to minimise the adverse e ects of urine on sperm motility 28 in any retrograde emission. The retrograde specimen was then obtained by catheterisation after the procedure was completed.…”
Section: Electroejaculationmentioning
confidence: 99%